A rare and fatal complication of ear syringing: Rupture of pseudoaneurysm at petrous internal carotid artery - Santosh Kumar Swain; Satya Sundar Gajendra Mohapatra (Archives of Trauma Research, 2018)
Ear syringing is a common procedure done for cleaning wax from the ear canal. Rupture of the pseudoaneurysm at the petrous part of the internal carotid artery (ICA) due to ear syringing is an extremely rare incidence in clinical practice. Sudden and profuse bleeding from the ear is the clinical presentation in case of ruptured pseudoaneurysm of ICA at the petrous part. Presence of the cholesteatoma at the middle ear cleft may be an etiology causing rupture of the pseudoaneurysm at the petrous part of the ICA, but the forceful ear syringing is an uncommon cause for the rupture of pseudoaneurysm. Radiological imaging is an important tool for the diagnosis. Endovascular technique is often used for the treatment of pseudoaneurysm of the ICA. Here, we are reporting an uncommon complication of forceful ear syringing making rupture of the pseudoaneurysm of petrous ICA leading to fatal spontaneous and profuse bleeding from the ear.